Validity of Lampetra pacifica (Petromyzontiformes: Petromyzontidae), a brook lamprey described from the lower Columbia River Basin - Reid, Stewart B.; Boguski, David A.; Goodman, Damon H.; Docker, Margaret F. (Zootaxa, 2011)
The Pacific Brook Lamprey, Lampetra pacifica Vladykov, 1973 was described from the lower Columbia River Basin near Portland, Oregon. Subsequently, L. pacifica has generally been treated as a junior synonym of the Western Brook Lamprey, L. richardsoni Vladykov and Follett, 1965, a species described from the Fraser River Drainage east of Vancouver, British Columbia. We reexamine the available morphological data used by previous authors (trunk myomere counts), report on recent collections from the Columbia Basin, and reinterpret the trunk myomere data in the context of recent genetic sampling from the same populations. Populations of L. pacifica are distinguished from those of L. richardsoni by trunk myomere counts of 53–60 (means 59), respectively, and by genetic sequence divergence (cyt b) of 2.85 to 3.20%. We find no support for placing L. pacifica in the synonymy of L. richardsoni and recognize L. pacifica as a valid species. However, we recognize that there is considerable unresolved diversity in the western North American lampreys and recommend restriction of L. pacifica to the Columbia Basin, suggesting that unresolved populations of Lampetra brook (non-parasitic) lampreys outside the basin with mean trunk myomere counts below 59 be referred to as L. cf. pacifica, until further systematic information is available.